Efektivitas Model Pembelajaran Quantum Teaching Terhadap Keterampilan Menulis Cerita Dongeng Siswa Kelas III SDN Kecil To’pae Kabupaten Enrekang - Nurfitriani Nurfitriani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the effectiveness of using the Quantum Teaching model on the fairy tale writing skills of class III students at SDN Kecil Topae, Enrekang Regency. This research is pre-experimental researchin the form of One Group Pretest-Posttest research. The population of this research is class III students at SDN Kecil To’pae in Enrekang Regency which consists of one class, namely 9 students. The research instrument used was a fairy tale writing test. The data obtained was then analyzed using descriptive statistical data analysis and inferential statistical data analysis. The result of this research show that the pretest result show that the average student learning score is 58,3 with categories, very high 0%, high 33,33%, medium 33,33%, low 33,33% and very low 0%. And the average score for posttest learning outcomes after using Quantum Teaching is 84,44 with categories very high 66,66%, high 33,33%, medium 0%, low 0%, very low 0%. These variations show that there is a significant influence of using the effectiveness Quantum Teaching learning model on fairy tale writing skills. Based on the description above, it can be concluded that the Quantum Teaching learning model is effectively used in learning to write fairy tales in class III students at SDN Kecil To’pae, Enrekang Regency.